2021
DOI: 10.11604/pamj.2021.39.149.26467
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and its implications for cervical cancer treatment and prevention in Zimbabwe: perspectives and recommendations

Abstract: Cervical cancer is the leading gynaecological malignancy in Zimbabwe, constituting 33% of all female cancers in 2016. Primary prevention through vaccination and secondary prevention through screening are important public health interventions to reduce the cervical cancer burden. Unfortunately, the ongoing COVID-19 pandemic has brought unprecedented challenges to healthcare delivery, posing threats to prevention efforts at a time when the public health sector is extremely fragile. The fragility of the sector ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…In addition to that, COVID-19 has also reduced vaccine access and disrupted vaccine administration services. A study reported that the impact of the pandemic caused the shortage of personal protective equipment leading to fear and increased anxiety among healthcare workers ( 13 ). The study highlighted the disruption to the global trade and supply chains leading to the shortage of HPV vaccination caused by the COVID-19 pandemic ( 13 ).…”
Section: Impact Of Pandemic Toward Global Hpv Immunization Programmentioning
confidence: 99%
“…In addition to that, COVID-19 has also reduced vaccine access and disrupted vaccine administration services. A study reported that the impact of the pandemic caused the shortage of personal protective equipment leading to fear and increased anxiety among healthcare workers ( 13 ). The study highlighted the disruption to the global trade and supply chains leading to the shortage of HPV vaccination caused by the COVID-19 pandemic ( 13 ).…”
Section: Impact Of Pandemic Toward Global Hpv Immunization Programmentioning
confidence: 99%
“…However, this reduction was predominantly oberserved at the early stage of the pandemic, and it gradually recovered up as the epidemic continued 35,36 . It's worth thinking about that preventive health services in undevelped and developing countris took a severe hit and have been the slowest to resume baseline services 37,38 . Similar with the most other countries, patients in China for HPV detection was sharply decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the Coronavirus Disease 2019 (COVID-19) pandemic has likely exacerbated many barriers to CC screening. Disruptions to health services, changes in healthseeking behaviors [27,28] as well as indirect economic effects [29] have likely resulted in reduced access and demand for CC screening and treatment services in the short and long term. The COVID-19 pandemic has likely also widened inequities in screening and treatment…”
Section: Plos Medicinementioning
confidence: 99%